Pietra su pietra: materialità e drammaturgia nella Niobe di Eschilo - Ozbek, Leyla (Lexis, 2022)
This paper analyses “the force of things” (Bennett 2010, 1) in Aeschylus’ Niobe, in particular the function of two material props (in a broader sense): the tomb of Niobe’s children and her mourning veil. These will be examined through both textual evidence and visual representations of the myth. Aristoph. Frogs 911-20 (test. 120 R) describes Niobe as seated, veiled, and silent for half of Aeschylus’ play (cf. also Vit. Aeschyl. 5-6 = test. 1.19-23 R). With such a static plot, material props are crucial; from a cognitive, physical, and psychological point of view they deeply affect the main character, as well as the other characters (including the chorus) and the spectators, who experience Niobe’s feelings through her contact with the material medium. The physical and psychological relationship between Niobe and the tomb affects her communication with the other characters, her own perception of reality and her capability to act. The grave locks Niobe into her grief, preventing her from moving forward – and physically away from it – and even from communicating with the outer world. The mourning veil is the material expression of this interrupted relationship. It acts as a material barrier, preventing communication between Niobe and the other characters: it weakens her physical and cognitive perception of the world, as well as her capacity to act, ‘sealing’ the character in her silence. Moreover, the veil separates Niobe from the world of the living, entrapping her in an exclusive relationship with her dead children.